Laurence-Moon-Biedl Syndrome - J Gordon Millichap (Pediatric Neurology Briefs)
Thirty-two patients with a form of Laurence-Moon-Biedl syndrome are reported from the Departments of Medicine, Ophthalmology, Radiology, and Community Medicine, Memorial University, St. John's, Newfoundland, Canada.